Motivación en la sombra: scoping review sobre la personalidad oscura desde la Teoría de la Autodeterminación - Berrocal, Gabriela (2026)
Dark personality has been associated with multiple forms of maladjustment and impaired well-being; however, the motivational mechanisms underlying these relationships have rarely been integrated in a systematic manner. This scoping review aimed to systematically map and analyze empirical evidence on the relationship between the Dark Factor of personality and the motivational processes proposed by Self-Determination Theory (SDT). Following PRISMA-ScR guidelines, searches were conducted in Scopus and APA PsycNet, yielding 12 empirical studies. Findings indicate that dark personality traits are consistently associated with greater frustration of the basic psychological needs for autonomy, competence, and relatedness, as well as with more controlled forms of motivation and amotivation. These patterns are linked to psychological, behavioral, and functional outcomes such as academic disengagement, stress, burnout, and compulsive behaviors. Moreover, when these traits are expressed in positions of authority, they may take on a contextual character, shaping more controlling climates that, from an SDT perspective, are associated with heightened need frustration and poorer motivational quality. Rather than deriving direct implications for practice, this review serves a guiding function for future research by identifying gaps in the understanding of regulatory processes, psychological adaptation, and behavioral manifestations. Longitudinal, experimental, and integrative studies are needed to clarify mechanisms, directionality, and conceptual integration.